Kemampuan pemecahan masalah matematik mahasiswa melalui pembelajaran mathematic in context - Nanang Nanang (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2018)
The purpose of this research is to know the difference of Mathematics Problem Solving (KPMM) of PGSD STKIP Garut students between groups who get learning Mathematic In Context (MIC) with those who get conventional learning (PK) in Mathematics Elementary Class of Low Class. The analytical technique for testing the difference of KPMM from the two data groups was used the two-tension difference test (t-test) and the proportion test to determine the quality of KPMM from both groups. Based on the result of research indicate that KPMM student of PGSD on MIC learning is significantly better than student who get PK. The quality of KPMM ability of the students who get MIC learning is in sufficient qualification classification, whereas KPMM students who get PK are in less classification.Keywords: Mathematical problem solving, mathematic in context